Physico-chemical parameters of soft and mature cheeses from milk from different breeds of goats - Karban, Y. (Scientific Progress & Innovations, 2024)
The work was aimed at researching the physical and chemical parameters of soft and mature cheeses in different periods of the year. The research was conducted in the conditions of Dobro-kraft FG and the Milk Lokal Product expert center on the basis of the Poltava State Agrarian University. For the experiment, 3 groups of goats were formed: the first – goats of the Zaanen breed, the second – of the Anglo-Nubian breed, the third – of the Alpine breed. To study cheese, milk was collected from goats of different breeds and at different times of the year (spring, summer, and autumn), and cheese was cooked according to technological maps for the production of soft fresh and mature cheeses. The soft cheese was delivered to the laboratory on the second day after preparation. Ripe cheese was placed for ripening in the basement at an air temperature of 10 °C and a relative humidity of 60–70 % for a period of 6 months. In the process of research, the physicochemical indicators of soft and mature cheese were determined, such as: mass fraction of fat in dry matter, mass fraction of moisture, mass fraction of kitchen salt, mass fraction of protein. It was established that the physicochemical parameters of soft and mature goat cheese are different and depend on the breed and season. Thus, when studying soft cheese at different times of the year, the minimum indicator of the mass fraction of fat in dry matter in this product was in Zaanen goats, and in Anglo-Nubian goats it was the maximum, where the maximum difference was 9.4 % (р<0.01) (spring) and 10.8 % (p<0.001) (autumn). At the same time, soft cheese from alpine goats was characterized by probably lower moisture content compared to other studied breeds. Determination of the quality of mature goat cheese in the spring period established a probable difference in the mass fraction of fat and protein in the dry matter, where the minimum indicator was observed in the Zaanen breed, which is probably smaller compared to the Anglo-Nubian and Alpine breeds. According to the mass fraction of moisture, there is an inverse pattern of redistribution of indicators in these breeds of goats. Anglo-Nubian and Alpine goats are the most suitable for making cheese for the production of soft and mature goat cheese. The most biologically complete soft cheeses are made in the spring and autumn periods of the year, and mature cheeses are made in the summer and autumn.